Between the Sword and the Wall : The Santos Peace Negotiations with the Revolutionary Armed Forces of Colombia - Kline, Harvey F. (Book collections on Project MUSE., 2020)
"Chronicles the peace process negotiations between Colombian president Juan Manuel Santos and the Marxist Revolutionary Armed Forces of Colombia"--